2022
DOI: 10.3389/fnagi.2022.905035
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index related to executive function and hippocampal subregion volume in subjective cognitive decline

Abstract: ObjectiveThis study aims to explore whether body mass index (BMI) level affects the executive function and hippocampal subregion volume of subjective cognitive decline (SCD).Materials and methodsA total of 111 participants were included in the analysis, including SCD (38 of normal BMI, 27 of overweight and obesity) and normal cognitive control (NC) (29 of normal BMI, 17 of overweight and obesity). All subjects underwent the Chinese version of the Stroop Color-Word Test (SCWT) to measure the executive function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Adiposity over the life course is associated with brain atrophy, white matter changes, and blood brain barrier integrity due to the presence of inflammatory markers and cytokines which may increase the risk of cognitive decline (West et al 2017). Central adiposity is a risk factor of comorbidities such as hypertension, diabetes and hyperlipidemia which are also associated with dementia (Chen et al 2022). Besides that, increased waist circumference is a component of metabolic syndrome which induces insulin resistance, hyperglycemia, dyslipidemia and hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Adiposity over the life course is associated with brain atrophy, white matter changes, and blood brain barrier integrity due to the presence of inflammatory markers and cytokines which may increase the risk of cognitive decline (West et al 2017). Central adiposity is a risk factor of comorbidities such as hypertension, diabetes and hyperlipidemia which are also associated with dementia (Chen et al 2022). Besides that, increased waist circumference is a component of metabolic syndrome which induces insulin resistance, hyperglycemia, dyslipidemia and hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity, as well as HFD diet consumption, and metabolic disorders, such as diabetes mellitus, are widely recognized as inducing impairments in brain structure and function in the form of memory dysfunction, as well as neurodegenerative diseases [ 37 ]. Furthermore, magnetic resonance imaging studies have demonstrated that regional brain atrophy and changes in gray and white matter are observed in patients with obesity, providing new insights into the relationship between obesity and cognitive decline from the imaging perspective [ 37 , 38 , 39 , 40 ]. Furthermore, a higher BMI is correlated with a lower gray matter volume in the prefrontal, temporal, insular, and occipital cortexes; thalamus; putamen; amygdala; and cerebellum, mediating the negative effects on memory performance [ 41 ].…”
Section: Obesity Induces Cognitive Declinementioning
confidence: 99%